Design and Optimization of Planar Inverted F Antenna (PIFA) for Wireless Applications - N. Taban, Iman; H. Khidhir, Ali; A. Naser, Ahmed (Al-Nahrain Journal of Science, 2023)
For 5G communication networks, including Long-Term Evolution Advanced mobile communication services, PIFA antenna is proposed. The proposed antenna structure is consisting of substrate, ground plane, shorting plate and feeding post connected to the ground plane. This antenna has been design based on a FR-4 has relative permittivity of 4.3 it has a volume of (120´60´1.5) mm3. The experimental results of the Planar Inverted F Antenna (PIFA) that have been measured at the range from (3-4 ) GHz of frequency experimentally using the Site Master (Anritsu S362E), it has been demonstrated that the return loss, bandwidth, VSWR, and impedance are -41.15dB, 510 MHz, 1.04 and 48.414 Ω respectively at resonant frequency 3.5 GHz. The theoretical and practical values are so close to each other which justifies the antenna’s excellent fit.